2015
DOI: 10.1080/01490451.2013.878418
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Microscopic Green Algae (Chlorophyta) in Calcifying Biofilms of Two Karstic Streams in Germany

Abstract: For the first time the diversity of microscopic green algae (Chlorophyta) from calcified biofilms of karstic streams was analyzed using a combined approach based on pure cultures, i.e., 18S rRNA gene sequencing and microscopic analyses. Our study focused on two creeks in Germany. A considerable diversity of 34 species of green microalgae comprising three classes, the Trebouxiophyceae, Chlorophyceae and Ulvophyceae, was recovered. The biofilms of both streams were rather different in their species compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In the class of Pyramimonadophyceae there exist phytoplankton quite important in the marine food web (Jónasdóttir, 2019) while microalgae belonging to other underrepresented classes (Ulvophyceae, Chlorophyceae, Trebouxiophyceae etc.) play important role in the food web of streams (Hodač et al, 2015). Collecting more data records in those marginally represented classes will surely enable e cient data use and contribute to the conservation and sustainable use of their biodiversity.…”
Section: -Discussion and Conclusionmentioning
confidence: 99%
“…In the class of Pyramimonadophyceae there exist phytoplankton quite important in the marine food web (Jónasdóttir, 2019) while microalgae belonging to other underrepresented classes (Ulvophyceae, Chlorophyceae, Trebouxiophyceae etc.) play important role in the food web of streams (Hodač et al, 2015). Collecting more data records in those marginally represented classes will surely enable e cient data use and contribute to the conservation and sustainable use of their biodiversity.…”
Section: -Discussion and Conclusionmentioning
confidence: 99%
“…In the class Pyramimonadophyceae, phytoplankton are quite important in the marine food web (Jónasdóttir, 2019), while microalgae belonging to other underrepresented classes (Ulvophyceae, Chlorophyceae, Trebouxiophyceae, etc.) play an important role in the food web of streams (Hodač et al, 2015). Collecting more data records in those marginally represented classes will surely enable e cient data use and contribute to the conservation and sustainable use of their biodiversity.…”
Section: -Discussion and Conclusionmentioning
confidence: 99%
“…Since several decades, the cave microbiome has been studied for several reasons [14] such as medical or pharmaceutical interests (e.g., research of antibio lm compounds) [15] and cave preservation (e.g., Paleolithic drawings and rock paintings curation) [16,17,18]. These studies have been carried out using a large set of microorganism identi cation technics such as microscopic methods [19,20], isolation and culture in laboratory [21], cloning followed by Sanger sequencing [22,23,24], ampli ed ribosomal DNA restriction analysis [25] or high throughput sequencing [6,26,27,28]. Results of these studies have demonstrated that cave microorganisms developing inside bio lms may be involved in speleogenesis processes.…”
Section: Introductionmentioning
confidence: 99%
“…Results of these studies have demonstrated that cave microorganisms developing inside bio lms may be involved in speleogenesis processes. Indeed, it has been reported that the complex microbial communities are capable of re ecting in substantial rock alterations, involved in calci cation processes [21,29,30,31], formation of new structures [32], corrosion of the mineral surfaces [4] and cave expansion [1,33]. Thus, the biodeterioration process is of great concern to cave owners and managers who nd themselves faced with a dual problem: the esthetic impact of bio lms [34,35,36] and the biodeterioration [31,37].…”
Section: Introductionmentioning
confidence: 99%